Pax6 Mediates ß‐Catenin Signaling for Self‐Renewal and Neurogenesis by Neocortical Radial Glial Stem Cells. (January 2014) - Gan, Qini; Lee, Albert; Suzuki, Ryusuke; Yamagami, Takashi; Stokes, Arjun; Nguyen, Bao Chau; Pleasure, David; Wang, Junjiang; Chen, Hong‐Wu; Zhou, Chengji J.
Abstract The Wnt/ß‐catenin pathway is a critical stem cell regulator and plays important roles in neuroepithelial cells during early gestation. However, the role of Wnt/ß‐catenin signaling in radial glia, a major neural stem cell population expanded by midgestation, remains poorly understood. This study shows that genetic ablation of ß‐catenin with hGFAP‐Cre mice inhibits neocortical formation by disrupting radial glial development. Reduced radial glia and intermediate progenitors are found in the ß‐catenin‐deficient neocortex during late gestation. Increased apoptosis and divergent localization of radial glia in the subventricular zone are also observed in the mutant neocortex. In vivo and in vitro proliferation and neurogenesis as well as oligodendrogenesis by cortical radial glia or by dissociated neural stem cells are significantly defective in the mutants. Neocortical layer patterning is not apparently altered, while astrogliogenesis is ectopically increased in the mutants. At the molecular level, the expression of the transcription factor Pax6 is dramatically diminished in the cortical radial glia and the sphere‐forming neural stem cells of ß‐catenin‐deficient mutants. Chromatin immunoprecipitation and luciferase assays demonstrate that ß‐catenin/Tcf complex binds to Pax6 promoter and induces its transcriptional activities. The forced expression of Pax6 through lentiviral transduction partially rescues the defective proliferation and neurogenesis by ß‐catenin‐deficient neural stem cells. Thus, Pax6 is a novel downstream target of the Wnt/ß‐catenin pathway, and ß‐catenin/Pax6 signaling plays critical roles in self‐renewal and neurogenesis of radial glia/neural stem cells during neocortical development. Stem Cells2014;32:45–58